Significance of thermal conductivity and variable density on heat and mass transfer of MHD second-grade nanofluid along high-temperature polymer surface - Nidhal Ben Khedher; Zia Ullah; Md Mahbub Alam; Saleh Al Arni; Isam Elbadawi; O.D. Makinde; Mohamed Boujelbene (Case Studies in Thermal Engineering)
The novelty of current research is to investigate exponential thermal density and thermal conductivity effect on heat-mass transmission in second-grade magneto nanofluid along stretching surface with thermal-solutal slip boundary conditions. The well define similarity transformation is applied on the couple of partial differential equations (PDEs) to transform into ordinary differential equations (ODEs). The Newton-Raphson and central difference technique is used to linearize these equations. Using MATLAB software technique, the results in graphical and numerical form are explored. The impact of various variables on fluid velocities, fluid temperatures and nanoparticle concentrations profiles are found graphically and numerically including, variable thermal conductivity, magnetic field, second-grade nanofluid factor, thermal slip, and concentration slip. The value of Nusselt number, Sherwood number and skin friction are found numerically for Prandtl number, density index, and thermophoretic factor. For asymptotic numerical outcomes, the following range of parameters such 0.1≤n≤1.4, 0.1≤Nt≤1.2, 0.1≤Nb≤2.0, 0.1≤ξ≤6.0, 0.1≤λ≤14.0, 0.1≤λ1≤8.0, 0.1≤α≤0.8, 0.1≤Pr≤10.0, 0.1≤Le≤3.5, 0.1≤Bt≤4.0, and 0.1≤Bc≤5.0 is used. It found that the higher value of thermal conductivity and thermal-concentration slip increases the velocity profile while magnetic field decreased it. Mass transmission and Nusselt rate are increased with increasing magnetic field. The maximum Nusselt number is explored for higher thermophoresis and density parameter. The noticeable amplitude in fluid velocity profiles is observed with thermal conductivity, temperature-concentration slip and buoyancy force effects under lower fluid density.